1994
DOI: 10.1084/jem.179.5.1529
|View full text |Cite
|
Sign up to set email alerts
|

T cell activation-associated hepatic injury: mediation by tumor necrosis factors and protection by interleukin 6.

Abstract: SummaryThis study investigates the molecular mechanisms underlying the induction of and protection from T cell activation-associated hepatic injury. When BALB/c mice were given a single intravenous injection of concanavalin A (Con A) (>10.3 rag/mouse), they developed acute hepatic injury as assessed by a striking increase in plasma transaminase levels within 24 h. Histopathologically, only the liver was injured while moderate infiltration of T cells and polymorphonuclear cells occurred in the portal areas and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
434
3
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 481 publications
(468 citation statements)
references
References 45 publications
27
434
3
4
Order By: Relevance
“…Our present observation that immunoinflammatory hepatitis can be induced in mice by a single i.v injection of Con A further confirms the original data by Tiegs' group [1,2], which were independently reproduced by others [3,8]. Most histological and immunopathogenic pathways described in those studies were also observed here.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our present observation that immunoinflammatory hepatitis can be induced in mice by a single i.v injection of Con A further confirms the original data by Tiegs' group [1,2], which were independently reproduced by others [3,8]. Most histological and immunopathogenic pathways described in those studies were also observed here.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, the histological and serological protection afforded by SF was accompanied by modifications of cytokine plasma levels, including reduced levels of IL-2, IFN-g and TNF-a, and augmented levels of IL-6. In this model TNF-a and IL-6 play a pathogenic and protective role [1][2][3], and the inhibition of TNF-a, with the simultaneous increase of IL-6 levels, may thus be central to the beneficial effects of SF. The ability of SF to reduce the blood levels of IL-2 and IFN-g may also be related to the protection afforded in this model by CsA and FK506, two immunosuppressants which selectively block IL-2 and IFN-g production [21].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Consistently with previous data, we observed that circulating levels of other inflammatory cytokines, such as IL-6, IL-1β, and IFN-γ peaked 3 h after ConA injection, and decreased sharply at later time points (Supporting Information Fig. 2A) [14]. In liver extracts, IL-1Ra levels increased gradually until 24 h after ConA injection, remained elevated up to 72 h, and returned to basal levels thereafter.…”
supporting
confidence: 91%